CGIAR GENDER science exchange 2022 book of abstracts - CGIAR GENDER Impact Platform (CGIAR GENDER Impact Platform, 2022)
This Book of Abstracts includes all abstracts presented at the CGIAR GENDER Science Exchange in Nairobi, Kenya, on October 12-14, 2022.